Body Image Dissatisfaction in the Contemporary Society: A Case Study of Nepali Youths - Manisha Khadga Yadav, (Interdisciplinary Journal of Management and Social Sciences, 2024)
People in recent times have become more focused on their body. They find a clear connection of their personality with their physical looks. Also, they attach their appearance or body-image with popular celebrities. In case people find their body image as good, they become satisfied, but if they find it below the 'ideal' type, they become upset. This practice of comparison indicates that people make negative remarks to their own body. Positive body image includes self-satisfaction with the appearance in terms of a given shape, size and weight of a body while negative body image means the dissatisfaction with shape, size and weight of body, and a perceived feeling of loss of sexuality. Notwithstanding the historical trend of women being more conscious of their preserved beauty, modern men have also been anxious of their body image and tried to be manly. This paper tries to explore what do people think about their bodies, how do they perceive their below-average body, what efforts they do make to change their average- or below-average body into a good-looking body, and how do they convert negative body image into a positive one. It finally argues that the labeling of own body is important for both men and women not only to learn types of bodies but also to adapt to them.